2020
DOI: 10.1136/jitc-2019-000316
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of α-galactosylceramide-pulsed antigen-presenting cells in patients with advanced or recurrent non-small cell lung cancer

Abstract: BackgroundInvariant natural killer T (iNKT) cells produce copious amounts of cytokines in response to specific glycolipid antigens such as α-galactosylceramide (αGalCer) presented by CD1d-expressing antigen-presenting cells (APCs), thus orchestrating other immune cells to fight tumors. Because of their ability to induce strong antitumor responses activated by αGalCer, iNKT cells have been studied for their application in cancer immunotherapy. In our previous phase I/II trial in non-small cell lung cancer (NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The increased immune response led to a median survival time of 31.9 months, compared with the median survival time of all patients being 18.6 months [142]. A follow-up study by Toyoda et al [105], examined overall survival time two years post-treatment and found a median overall survival of 21.9 months. Both studies demonstrate that α-GalCer-loaded-DCs can be an effective treatment option for NSCLC.…”
Section: Adoptive Transfer Of Dcs Presenting α-Galcermentioning
confidence: 99%
“…The increased immune response led to a median survival time of 31.9 months, compared with the median survival time of all patients being 18.6 months [142]. A follow-up study by Toyoda et al [105], examined overall survival time two years post-treatment and found a median overall survival of 21.9 months. Both studies demonstrate that α-GalCer-loaded-DCs can be an effective treatment option for NSCLC.…”
Section: Adoptive Transfer Of Dcs Presenting α-Galcermentioning
confidence: 99%
“…Similarly embryonic stem cell-derived DCs transfected in vitro to express an antigen as well as CCL21 and loaded with α-galactosylceramide, an antigen specific for invariant NK T cells [84], was able to mobilise both conventional and NK T cells and showed an increased anti-tumour effect [85]. The clinical potential of this approach was assessed in a phase II study in patients with advanced non-small cell lung carcinoma (NSCLC) [86]. Intra-tumoural administration of autologous dendritic cells (DC) transduced with an adenoviral (Ad) vector to express CCL21, resulted in enhanced tumour CD8 + T-cell infiltration as well as increased tumour PD-L1 expression [87].…”
Section: C-patient Derived Transfected Cellsmentioning
confidence: 99%
“…CD1D, a member of the CD1 family, is a class of non-polypeptide transmembrane glycoprotein molecules, which is widely expressed in thymocyte B cells, epidermal Langham cells, dendritic cells, and intestinal epithelial cells [40] . With function of antigen presentation similar to MHC I, CD1D can speci cally present antigens to NKT cells, make them activate and secrete a variety of cytokines, and directly or indirectly participate in the body's immune response [41] .Recently, a research about CD1d-binding glycolipid for iNKT-cell-based therapy showed a potent and effective treatment against human breast cancer [42] .Another clinical phase II study showed that intravenous administration of α-GalCer-pulsed antigen-presenting cells (APCs) prolonged overall survival for patients with advanced or recurrent non-small cell lung cancer [43] . (α-GalCer an exogenous glycolipid antigen extracted from sponges speci cally binding to CD1D molecule can activate NKT cells to exert immune effects [44] . )…”
Section: Discussionmentioning
confidence: 99%